Environmental Sustainability Assessment of Horticultural Systems: A Multi-Criteria Evaluation Approach Applied in a Case Study in Mediterranean Conditions - Francesco Montemurro; Alessandro Persiani; Mariangela Diacono (Agronomy, 2018)
An increasing interest and sensitivity of consumers and public opinion toward high-quality food products obtained with environmentally-friendly production methods has recently been detected. To this end, one of the key roles could be played by an environmental evaluation of the crop production. This research was performed to test a new multi-attribute decision model (DEXi-met) that is able to estimate the environmental sustainability of different agronomic practices in horticultural rotations. The model was used at the cropping system level on the basis of data from a long-term experiment in organic horticulture. It was tested on different cropping managements under climate change conditions. The DEXi-met mixed model (qualitative and qualitative basic attributes) generated four aggregated attributes to assess sustainability indicators (production capacity, soil, water and resources preservation, and biodiversity conservation) and the overall environmental sustainability. The model validation indicated that the introduction of agro-ecological services crops can increase the environmental sustainability of an organic cropping systems by promoting the whole soil–plant system equilibrium. The application of this tool could help maximize the efficient use of agronomical practices and quantify their environmental sustainability. DEXi-met could help agricultural advisors and policymakers schedule their decisions to find the right compromise between crop yield increase and the impact of agricultural activities.